Inflation inequality in Austria: A mid-term view on cost-of-living developments - Huber, Alexander W. (Wirtschaft und Gesellschaft, 2023)
I compute household-specific inflation rates for Austria for the period between 2016 and 2019. Data is provided by Statistics Austria’s Consumer Expenditure Survey for 2014/15 (“Konsumerhebung”) and contains household expenditures reaching the 3-digit COICOP level. I find a negative plutocratic bias, meaning that common types of measurement tend to understate CPI inflation. In the period covered, the distribution of inflation is characterized by large dispersion, meaning that the standard CPI inflation is not very representative for a large proportion of Austrian households. There is a clear negative relationship between income and inflation that is mainly driven by ownership status. Households living in rental accommodation are affected significantly more by inflation. I further find an urban-rural divide in the sense that households in larger cities are more likely to exhibit higher individual inflation rates than their counterparts in small municipalities. Considering household structures, single households exhibit significantly higher inflation. These effects remain significant even after controlling for ownership status. All in all, the results are strong arguments for paying greater attention to the issue of inflation inequality when it comes to wage setting, taxation or indexations, as there are potentially large distributional effects going unrecognized.